A novel in vitro cell model of the proteinase/antiproteinase balance observed in alpha-1 antitrypsin deficiency - Chen, Celine H.; Crisford, Helena; Scott, Aaron; Sapey, Elizabeth; Stockley, Robert A. (Frontiers in Pharmacology, 2024)
Background: Alpha-1 antitrypsin deficiency (AATD) is a genetic condition resulting from mutations in the alpha-1 antitrypsin (AAT) protein, a major systemic antiproteinase, resulting in reduced/no release of AAT disrupting the proteinase/antiproteinase balance. A sustained imbalance can cause structural changes to the lung parenchyma leading to emphysema. Predicting and assessing human responses to potential therapeutic candidates from preclinical animal studies have been challenging. Our aims were to develop a more physiologically relevant in vitro model of the proteinase/antiproteinase balance, and to assess whether the data generated could better predict the efficacy of pharmacological candidates to inform decisions on clinical trials together with expected biomarker responses.Methods: We developed an in vitro model assessing the proteinase/antiproteinase balance by the changes in the fibrinogen cleavage products of neutrophil elastase (NE) and proteinase 3 (PR3). This allowed the assessment of physiological and pharmaceutical neutrophil serine proteinase (NSP) inhibitors to determine the putative threshold where the maximal effect is achieved.Results: AAT significantly reduced NE and PR3 activity footprints, with the maximal reduction achieved at concentrations above 10 μM. The inhibitor MPH966 alone also significantly reduced NE footprint generation in a concentration-dependent manner levelling out above 100 nM but had no effect on PR3 footprint. At levels of AAT consistent with AATD, MPH966 had an additive effect reducing the NE activity footprint more than either inhibitor alone. Conclusion: Our results support an inhibitor threshold above which the activity footprint generation appears resistant to increasing dosage. Our model can support testing of inhibitors, confirming activity biomarkers as indicators of likely pharmaceutical efficacy, the assessment of NSP activity in the pathophysiology of emphysema, and the likely function of biological or pharmacological inhibitors in disease management.